2001
DOI: 10.1038/sj.ijo.0801583
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of leisure-time physical activity and occupational activity to the prevalence of obesity

Abstract: OBJECTIVE: To assess the interaction between leisure-time physical activity (LTPA) and occupational activity (OA) on the prevalence of obesity. DESIGN: Secondary data analysis of a population based cross-sectional US national sample (NHANES III). SUBJECTS: A total of 4889 disease-free, currently employed adults over age 20 y. MEASUREMENTS: Subjects body mass index (BMI) was categorized as (1) obese (BMI ! 30 kgam 2 ), or (2) non-obese (BMI`30 kgam 2 ). LTPA was divided into four categories: (1) no LTPA; (2) ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
160
5
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(178 citation statements)
references
References 34 publications
11
160
5
2
Order By: Relevance
“…While some inverse associations have been reported between occupational activity and obesity and its associated sequelae (King et al, 2001;Barengo et al, 2004;Mummery et al, 2005), others have found no association (Ball et al, 2001;GutierrezFisac et al, 2002). The majority of this work investigates Model 2 also includes occupational activity as specified in Model 1, results did not substantially differ so are not shown above.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While some inverse associations have been reported between occupational activity and obesity and its associated sequelae (King et al, 2001;Barengo et al, 2004;Mummery et al, 2005), others have found no association (Ball et al, 2001;GutierrezFisac et al, 2002). The majority of this work investigates Model 2 also includes occupational activity as specified in Model 1, results did not substantially differ so are not shown above.…”
Section: Discussionmentioning
confidence: 98%
“…populations from higher-income countries where leisuretime physical activity is far more prevalent, and studies have shown the interaction of leisure time and occupational activity to be quite complex (Burton and Turrell, 2000;Salmon et al, 2000;King et al, 2001;Evenson et al, 2003). However, in many developing countries, China included, adults acquire the majority of their daily physical activity in their working lives and leisure-time physical activity is relatively uncommon (Popkin, 1999;Caballero, 2001); thus highlighting the importance in considering occupation when assessing overall energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…While occupational activity is studied less frequently than other forms of activity, a number of studies have demonstrated the importance of work as a source of energy expenditure (Dorn, Cerny, Epstein et al, 1999;Evenson, Rosamond, Cai et al, 2003;King, Fitzhugh, Bassett et al, 2001;Salmon, Owen, Bauman et al, 2000). In developed countries such as the United States, those with the light occupational activity are more likely to have higher levels of leisure time activity (Burton & Turrell, 2000;Evenson, Rosamond, Cai et al, 2003;Salmon, Owen, Bauman et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, shifts from labor intensive to sedentary occupations may portend the removal of a source of energy expenditure important for weight maintenance and overall health status. While occupational activity is studied less frequently than leisure time physical activity, a number of studies have shown it to be an important source of energy expenditure that should not be neglected (Dorn, Cerny, Epstein, Naughton, Vena, Winkelstein et al, 1999;Evenson, Rosamond, Cai, Pereira, & Ainsworth, 2003;King, Fitzhugh, Bassett, McLaughlin, Strath, Swartz et al, 2001;Salmon, Owen, Bauman, Schmitz, & Booth, 2000). Relevant to shifting activity patterns we note that China has recently had a remarkable increase in the number of overweight adults (Bell, Ge, & Popkin, 2001;Gu, Reynolds, Wu et al, 2005;Popkin, 2001a;Zhou, Wu, Yang, Li, Zhang, & Zhao, 2002).…”
Section: Introductionmentioning
confidence: 91%
“…Although the primary treatment for obesity historically has been caloric restriction, a more promising treatment may consist of increased physical activity in addition to controlling energy intake. Physical exercise rapidly increases energy expenditure and has been associated with improved weight control (Brook et al, 1995;King et al, 2001;Wier et al, 2001). Exercise also causes a preferential utilization of fat, resulting in less fat in active individuals compared with sedentary controls.…”
Section: Introductionmentioning
confidence: 99%